PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISTEM PENDINGIN - Kabul Setiyo Purwoko; Slamet Priyanto (Jurnal Taman Vokasi, 2016)
This study aimed to know (1) the use of demonstration method could improve learning motivation of cooling system and (2) the use of demonstration method could improve learning motivation. This study was an action research. Data collection techniques used documentation and test. Data analysis technique used descriptive analysis and quantitative to know percentage of learning achievement. This study shows that (1) the use of demonstration method could improve learning motivation of cooling system. The students were used to learn by using demonstration method and they showed their activeness in learning process. (2)Â  The use of demonstration method could improve learning motivation. The average score of pre cycle was 56.25, cycle I was 63.28, cycle II was 72.81, and cycle III was 81.56.